2019
DOI: 10.1186/s13075-019-1948-1
|View full text |Cite
|
Sign up to set email alerts
|

Prostaglandin receptor EP4 expression by Th17 cells is associated with high disease activity in ankylosing spondylitis

Abstract: Background: Th17 cells are involved in the pathogenesis of ankylosing spondylitis (AS). However, the mechanism underlying enhanced Th17 cell accumulation in AS remains unknown. The prostaglandin E 2 receptor EP2/EP4 signaling pathway plays a critical role in the development of autoimmune Th17 cells. Interestingly, recent genomewide association studies (GWAS) have identified five risk alleles for AS in PTGER4, the gene encoding for EP4. The aim of this study was to reveal a possible link between EP4 and disease… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
17
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 29 publications
(19 citation statements)
references
References 63 publications
1
17
0
Order By: Relevance
“…Punicalagin-mediated reduced TNF- α , IL-1 β , IL-6, and NO serum levels in AS-induced mice illustrate the anti-inflammatory efficacy. Further, it has been shown that Janus kinases (JAK) are major transducers of cytokine signals in Th17 cells [ 40 , 41 ]. Th17 cells, which is a key player in AS, secrete various inflammatory mediators such as IL-17, IL- 6, IL-22, IL-26, interferon- (IFN-) γ , and TNF- α [ 8 ].…”
Section: Discussionmentioning
confidence: 99%
“…Punicalagin-mediated reduced TNF- α , IL-1 β , IL-6, and NO serum levels in AS-induced mice illustrate the anti-inflammatory efficacy. Further, it has been shown that Janus kinases (JAK) are major transducers of cytokine signals in Th17 cells [ 40 , 41 ]. Th17 cells, which is a key player in AS, secrete various inflammatory mediators such as IL-17, IL- 6, IL-22, IL-26, interferon- (IFN-) γ , and TNF- α [ 8 ].…”
Section: Discussionmentioning
confidence: 99%
“…The peripheral blood of patients with RA is characterised by a higher percentage of Th17 cells and the balance between Th17 cells and Treg cells is shifted 6. In RA patients, the Th17/Treg cell balance is not recovered by JAK inhibitors, although the percentage of Th17 cells is significantly suppressed (figure 1E).…”
mentioning
confidence: 98%
“…Furthermore, activation of prostaglandin E2 receptor 4 (EP4), the protein product of prostaglandin EP4 receptor (PTGER4) promotes development of Th17 cells by increasing the IL-23 expression level. PTGER4 polymorphisms have been shown to be associated with axSpA [ 61 ]. In addition to the increase in IL-23 secretion, it has been shown that prostaglandin E2 (PGE2) levels were significantly elevated in mice patellar and Achilles tendons in response to rigorous treadmill training [ 62 ].…”
Section: Cytokines As Danger Signals In Both the Gut And Enthesismentioning
confidence: 99%